2019
DOI: 10.3390/cryst9060323
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assemblies in Pb(II) Complexes with Hydrazido-Based Ligands

Abstract: Herein, we describe the synthesis and single crystal X-ray diffraction characterization of several Pb(II) complexes using Schiff base hydrazido-based ligands and different counterions (NO3−, I– and ClO4). In the three complexes reported in this work, the lead(II) metal exhibits a high coordination number (n > 8) and thus it is apparently not involved in tetrel bonding interactions. Moreover, the aromatic ligands participate in noncovalent interactions that play an important role in the formation of several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…These interactions can be visualized best by calculating Hirshfeld surface followed by highlighting areas corresponding to C•••C interactions (Figure 4c). Furthermore, by inspecting the shape-index surfaces we were able to confirm these interactions because of appearance of neighboring red and blue triangular map areas (red circles), which are characteristic for occurrence of π-π stacking [67,68].Both types of the supramolecular dimers,…”
Section: Crystal Structurementioning
confidence: 74%
“…These interactions can be visualized best by calculating Hirshfeld surface followed by highlighting areas corresponding to C•••C interactions (Figure 4c). Furthermore, by inspecting the shape-index surfaces we were able to confirm these interactions because of appearance of neighboring red and blue triangular map areas (red circles), which are characteristic for occurrence of π-π stacking [67,68].Both types of the supramolecular dimers,…”
Section: Crystal Structurementioning
confidence: 74%
“…These optimal interlayer distances are all fairly greater than the Pb-B bond length (2.122 Å) 31 and the Pb-N bond length (2.75 Å). 32 Therefore, Pb atoms of the per Pb atom at the optimized interlayer distance are higher than the typical binding energies due to weak vdW interactions. 33 This indicates that plumbene and hexagonal boron nitride are bound by other interactions, such as electrostatic interaction along with vdW interaction.…”
Section: Resultsmentioning
confidence: 99%
“…These optimal interlayer distances are all fairly greater than the Pb–B bond length (2.122 Å) 31 and the Pb–N bond length (2.75 Å). 32 Therefore, Pb atoms of the plumbene layer are expected not to form covalent bonds with B and N atoms of the hBN layer. The binding energies of the three patterns are negative, implying the stability of these structures.…”
Section: Resultsmentioning
confidence: 99%
“…Contrariwise, hemidirected lead(II) complexes present the coordination bonds only as a part of an encompassing globe [20]. Some of us and others [21][22][23][24][25][26][27][28][29][30][31][32][33] have demonstrated that hemidirected lead(II) complexes have a strong tendency to form non-covalent tetrel bonding interactions and semicoordination bonds. Tetrel bonding interactions are non-covalent bonds between any electron rich moiety and a Lewis acid atom belonging to group 14 of elements.…”
Section: Introductionmentioning
confidence: 99%